How to turn a team of experts into an expert medical team: guidance from the aviation and military communities. (1st October 2004) - Burke, C S; Salas, E; Wilson-Donnelly, K; Priest, H
Abstract : There is no question that interdisciplinary teams are becoming ubiquitous in healthcare. It is also true that experts do not necessarily combine to make an expert team. However when teams work well they can serve as adaptive systems that allow organisations to mitigate errors within complex domains, thereby increasing safety. The medical community has begun to recognise the importance of teams and as such has begun to implement team training interventions. Over the past 20 years the military and aviation communities have made a large investment in understanding teams and their requisite training requirements. There are many lessons that can be learned from these communities to accelerate the impact of team training within the medical community. Therefore, the purpose of the current paper is to begin to translate some of the lessons learned from the military and aviation communities into practical guidance that can be used by the medical community.